2016
DOI: 10.1159/000447023
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Muscle Strength in Haemodialysis Patients by Pinch and Hand Grip Strength and Comparison to Lean Body Mass Measured by Multifrequency Bio-Electrical Impedance

Abstract: Background: Muscle weakness is a risk factor for mortality in haemodialysis (HD) patients; we wished to determine whether measuring the composition of the arm with bioimpedance was associated with arm muscle strength. Methods: We measured pinch strength (PS) and hand grip strength (HGS) in 250 adult HD patients with corresponding post-dialysis multifrequency bioelectrical assessments with segmental body analysis. Results: Mean age 64.0 ± 15.6, 66% male and 45.6% diabetic. The maximum HGS in the dominant or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…7,16 Many kidney dialysis patients complain of physical tiredness, mental fatigue, and have reduced physical activity, 18 which often do not improve following the initiation of dialysis therapy, and may even be made worse by haemodialysis treatments. 19,20 Patients with chronic kidney disease treated by haemodialysis are more likely to suffer protein energy wasting leading to muscle loss, 21 and reduced muscle mass is associated with reduced physical activity and energy expenditure, 22 so increasing weakness and fatigue. The BDI-II score was associated with younger age, higher serum albumin, and anuria.…”
Section: Discussionmentioning
confidence: 99%
“…7,16 Many kidney dialysis patients complain of physical tiredness, mental fatigue, and have reduced physical activity, 18 which often do not improve following the initiation of dialysis therapy, and may even be made worse by haemodialysis treatments. 19,20 Patients with chronic kidney disease treated by haemodialysis are more likely to suffer protein energy wasting leading to muscle loss, 21 and reduced muscle mass is associated with reduced physical activity and energy expenditure, 22 so increasing weakness and fatigue. The BDI-II score was associated with younger age, higher serum albumin, and anuria.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic kidney disease treated by hemodialysis (HD) are at increased risk of losing muscle mass as a result of multiple factors, including dietary restrictions, metabolic acidosis, insulin resistance, urinary and dialysate protein losses, and reduced physical activity along with fatigue and self‐reported depression . Reports of studies using HGS measurements in HD patients have shown that HGS measurements are reliable and reproducible and not affected by the presence of an arterio‐venous fistula or the dialysis session . In addition, HGS weakness in HD patients is associated with increased mortality risk …”
mentioning
confidence: 99%
“…8,9 Reports of studies using HGS measurements in HD patients have shown that HGS measurements are reliable and reproducible and not affected by the presence of an arterio-venous fistula or the dialysis session. [10][11][12] In addition, HGS weakness in HD patients is associated with increased mortality risk. 13 As there has been recent concordance in defining sarcopenia first by a loss of muscle strength measured by HGS by both the European Working Group on Sarcopenia in Older People (EWGSOP) 3 and the North American Foundation for the National Institutes of Health Sarcopenia Project (FNIH), 4 we determined the prevalence of muscle weakness using these definitions as well as comparing muscle weakness with age-matched and gender-matched controls.…”
mentioning
confidence: 99%
“…We also noted an association between muscle wasting, using the FNIH Sarcopenia Project cut‐offs, and lower self‐reported fatigue scores. Although this may appear paradoxical, previous reports in dialysis patients have not shown a relationship between muscle mass and muscle strength, or physical activity in hemodialysis patients , and one study reported an inverse association between muscle mass measured by magnetic resonance imaging and physical activity . However, these studies typically measured muscle mass pre‐dialysis, and measurement of muscle mass is affected by dialysis, with more reliable measurements obtained post‐dialysis using magnetic resonance imaging and bioimpedance , after allowing time for re‐equilibration.…”
Section: Discussionmentioning
confidence: 96%